Global Project Examining Link between Dietary Intake and Breast Cancer - Mosley, Mary (MD Conference Express, 2014)
The International Breast Cancer and Nutrition (IBCN) Project was launched in 2010 and is the first global effort to elucidate the relation between diet, genetics, and the development of breast cancer. This article reviews new research approaches for the IBCN and some preliminary data from Phase 1 of the study on the primary prevention of breast cancer and other noncommunicable diseases.